Comparison between Paediatric Advanced Warning Score (PAWS) and Paediatric Early Warning Score (PEWS) in Predicting Intensive Care Unit Admissions in Children - Hitha Rose Mathew; Sweta Shanbhag; Habeeb Ullah Khan (Journal of Medical Evidence)
Background: Children with varying severity of illness seek medical care and early identification of patients at risk of clinical deterioration along with appropriate level of care are integral components of high-quality medical care. The paediatric advanced warning score (PAWS) is a newer scoring system which takes additional parameters such as temperature, oxygen saturation and alert, verbal, pain, unresponsive (AVPU) scale compared to the widely used paediatric early warning score (PEWS). Aims: The aim of this study was to compare the utility of PAWS with PEWS for predicting intensive care unit (ICU) admissions in children. Materials and Methods: We conducted a prospective observational study, which included 1000 children aged 1 month to 15 years who presented to the emergency department. Focussed clinical assessment was done and PAWS and PEWS were assigned. Cutoff scores for predicting paediatric ICU admission for each of these scores were derived using the receiver operating characteristics (ROC) curve, sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV). Results: Out of 1000 children included in the study, 169 (16.9%) patients required admission – 107 to ward and 62 to ICU. For PAWS, the area under curve (AUC) for predicting ICU admission for a cutoff score of ≥3 was 0.969 (P < 0.0001) with sensitivity, specificity, PPV and NPV of 88%, 99%, 96.5% and 99.2%, respectively. For PEWS, AUC for predicting ICU admission for a cutoff score of ≥3 was 0.946 (P < 0.0001) with sensitivity, specificity, PPV and NPV of 41.9%, 99.6%, 89.6% and 99.2%, respectively. Conclusion: PAWS can serve as a better screening tool for prediction of ICU admission in children, as compared to PEWS.